Pengaruh Media Sosial Youtube Terhadap Partisipasi Politik Pada Mahasiswa - Irbah Muthiah Fuadah; Septiawan Santana Kurnia (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. This study is titled The Influence of YouTube Social Media on Political Participation Among Students (A Simple Linear Regression Study on the Influence of Political Content on the @Pandji.Pragiwaksono YouTube Account on the Political Participation of Fikom Universitas Islam Bandung Students Class of 2021 Who Watch Pandji Pragiwaksono's Content). The study employs the media exposure theory, which encompasses the dimensions of frequency, attention, and duration. The method used is simple linear regression analysis to measure the causal relationship between YouTube social media as the independent variable and student political participation as the dependent variable. Data analysis includes descriptive tests, classical assumption tests, simple linear regression tests, t-tests, and the coefficient of determination, conducted using SPSS version 25. The research population comprises 314 Fikom Unisba students from the Class of 2021 who have watched content on the @Pandji.Pragiwaksono YouTube channel, with 76 respondents selected through a survey targeting Class of 2021 students in Universitas Islam Bandung’s Faculty of Communication (Fikom) who watch Pandji Pragiwaksono's content. Data was collected using an online questionnaire. The findings show that the frequency, attention, and duration of media exposure significantly influence students' political participation, as evidenced by the t-value being greater than the t-table value. These findings highlight that YouTube political content can enhance political awareness and engagement among young people. This study provides insights for content creators to develop more effective social and political issue-based materials. Abstrak. Penelitian ini berjudul Pengaruh Media Sosial YouTube terhadap Partisipasi Politik pada Mahasiswa. Studi ini menganalisis pengaruh konten politik di akun YouTube @Pandji.Pragiwaksono terhadap partisipasi politik mahasiswa Fikom Universitas Islam Bandung Angkatan 2021 yang menonton kontennya. Penelitian menggunakan teori terpaan media (frekuensi, atensi, dan durasi) serta metode regresi linier sederhana untuk mengukur hubungan antara YouTube sebagai variabel independen dan partisipasi politik sebagai variabel dependen. Analisis data mencakup uji deskriptif, asumsi klasik, regresi linier sederhana, uji-t, dan koefisien determinasi menggunakan SPSS versi 25. Populasi penelitian adalah 314 mahasiswa Fikom Unisba Angkatan 2021, dengan 76 responden yang dipilih melalui survei daring.Hasil penelitian menunjukkan bahwa frekuensi, atensi, dan durasi terpaan media berpengaruh signifikan terhadap partisipasi politik mahasiswa, dibuktikan oleh nilai t-hitung yang lebih besar dari t-tabel. Temuan ini menunjukkan bahwa konten politik di YouTube dapat meningkatkan kesadaran dan keterlibatan politik generasi muda. Penelitian ini memberikan wawasan bagi pembuat konten untuk mengembangkan materi berbasis isu sosial dan politik yang lebih efektif.